California’s endemic Cornus sessilis in Ukraine - S. V. Klymenko; A. P. Ilyinska; A. V. Kustovska; N. V. Melnychenko (Regulatory Mechanisms in Biosystems, 2021)
Global climate change and increased land use lead to the loss of biodiversity at all levels of the organization of living organisms – ecosystems, species, landscape population, genetic, molecular biological levels, etc. The reaction of plants to anthropogenic impact, according to experts, may be even stronger than postglacial changes. A shift in the thermal isotherm will cause the plants to either move and adapt, or disappear. Endemic species that make up “biodiversity hotspots” require special attention. Cornus sessilis Torr. ex Durand, the object of our research, is part of one of these points – the California Floristic Province. Researchers are now focusing their efforts on developing a climate change – related biodiversity management strategy. In the case of the threat of extinction of the species in nature, there is a important method of preserving it in culture (ex situ). M. M. Gryshko National Botanical Garden at the National Academy of Sciences of Ukraine (the NBG) pays great attention to the introduction of rare endemic species from the different geographical and floristic regions of the world. The gene pool of Cornus L. s. l. in the NBG consists of more than 30 species and 40 cultivars including the insufficiently researched and little-known Californian endemic C. sessilis. In Europe, it has been grown since 2017 only in Chateau Perouse Botanic Gardens (Saint-Gilles, France) and in Ukraine only the NBG has it. In this article we evaluate the life cycle of the development C. sessilis under conditions of introduction different from the conditions of its natural area. To do this, we used the classic traditional methods of the research on the process of introduction, in particular, botanical plant identification, visual observation, phenology, comparative morphology and biometrics. Morphological descriptors (life form, colour and texture of bark, leaf shape, pubescence character, structure of generative and vegetative buds, inflorescences, flowers, fruits and endocarp) of C. sessilis genotypes introduced to the NBG are identical to those of plants from their natural habitats. The weight of fruits and endocarps were determined by us for the first time. The results of biometric analysis of the size of leaves and fruits showed that the plants of C. sessilis grown in the NBG had the larger leaf blades, but the smaller fruits as compared to those in the wild. In the NBG the plants underwent a full cycle of seasonal development (from the deployment of buds to the leaf fall, inclusive) for 229 days. In general, the phenological strategy of C. sessilis genotypes introduced in the NBG corresponds to that of other species of Cornus s. str., including C. mas L. Our results indicate that C. sessilis, California’s rare endemic species new to Ukraine, has adapted to the new conditions – the plants bear fruits and produce seeds. The experience of successful introduction makes it possible to cultivate a new species to expand the diversity of food, medicinal and reclamation plants of the family Cornaceae as well as the use in synthetic breeding to obtain new cultivars with valuable biological and economic properties. Cornus sessilis compatibility test as rootstocks for other species is important for clarifying the theoretical issues of family ties of species Cornaceae and practical – for widespread reproduction of the required cultivars C. mas breeding in the NBG on a potentially compatible rootstock C. sessilis.